Photoprotection mechanisms in Quercus ilex under contrasting climatic conditions - Camarero, Jesús Julio; Olano, José Miguel; Arroyo Alfaro, Sandra Jackeline; Fernández-Marín, Beatriz; Becerril, José Maria; García-Plazaola, José Ignacio (Flora - Morphology, Distribution, Functional Ecology of Plants, 2012)
Acclimation to local conditions may produce adaptive responses in plants subjected to diverse climatic stresses. However, it has not been assessed how local adaptation and phenotypic plasticity contribute to photoprotection mechanisms in response to contrasting climatic conditions in Mediterranean tree species. We analyzed photoprotectionmechanisms inmature trees oftheMediterranean evergreen oak Quercus ilex at three sites with contrasting climatic conditions, i.e. xeric, continental and mesic sites. We studied morphological and physiological parameters indicative of photoprotection in adult trees in the ﬁeld. In order to establish whether these parameters were genetically determined we compared adults with seedlings germinated from acorns of the three sites and grown under common greenhouse conditions. In the ﬁeld we found no signiﬁcant differences in most of the physiological parameters in summer, but in winter the adulttrees fromthe continental site were photoinhibited. In contrast,there were signiﬁcant differences between seedlings in most photoprotective parameters evaluated. Morphological traits such as trichome density and leaf reﬂectance differed between populations, both in ﬁeld-grown trees and in greenhouse-grown seedlings, being higher in all cases in plants from the xeric site than elsewhere. Our ﬁndings suggest the existence of constitutive differences in leaf photoprotection mechanisms among Q. ilex populations. These divergences may represent an inherent source for more stress tolerant ecotypes in the face of changing climatic conditions.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: ecotypes; Holm oak; Mediterranean; photoprotection; Trichomes

Trichomes and photosynthetic pigment composition changes: responses of Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L. to Mediterranean stress conditions - Morales, F.; Abadia, A.; Abadía, J.; Montserrat, G.; GIL-PELEGRÍN, E. (Trees, 2002)
Sun and shade leaves of two Mediterranean Quercus species, Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L., were compared by measuring leaf optical properties, photosynthetic pigment composition and photosystem II efficiency. The presence of trichomes in the adaxial (upper) leaf surface of Q. ilex subsp. ballota seems to constitute an important morphological mechanism that allows this species to maintain a good photosystem II efficiency during the summer. Q. coccifera has almost no trichomes and seems instead to develop other physiological responses, including a smaller light-harvesting antenna size, higher concentrations of violaxanthin cycle pigments and a higher (zeaxanthin + antheraxanthin)/(violaxanthin + antheraxanthin + zeaxanthin) ratio. Q. coccifera was not able to maintain a good photosystem II efficiency up to the end of the summer. In Q. ilex subsp. ballota leaves, natural loss or mechanical removal of adaxial-face leaf trichomes induced short-term decreases in photosystem II efficiency. These changes were accompanied by deepoxidation of violaxanthin cycle pigments, suggesting that the absence of trichomes would trigger physiological responses in this species. Our data have revealed different patterns of response of Q. ilex subsp. ballota and Q. coccifera facing the stress conditions prevailing in the Mediterranean area.
Keywords: adaxial epidermis; photoprotection; Quercus; Trichomes

Trichomes and photosynthetic pigment composition changes: responses of Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L. to Mediterranean stress conditions - Morales, F; Abadía, A; Abadia, J; Montserrat, G; Gil-Pelegrín, E (Trees, 2002)
Sun and shade leaves of two Mediterranean Quercus species, Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L., were compared by measuring leaf optical properties, photosynthetic pigment composition and photosystem II efficiency. The presence of trichomes in the adaxial (upper) leaf surface of Q. ilex subsp. ballota seems to constitute an important morphological mechanism that allows this species to maintain a good photosystem II efficiency during the summer. Q. coccifera has almost no trichomes and seems instead to develop other physiological responses, including a smaller light-harvesting antenna size, higher concentrations of violaxanthin cycle pigments and a higher (zeaxanthin + antheraxanthin)/(violaxanthin + antheraxanthin + zeaxanthin) ratio. Q. coccifera was not able to maintain a good photosystem II efficiency up to the end of the summer. In Q. ilex subsp. ballota leaves, natural loss or mechanical removal of adaxial-face leaf trichomes induced short-term decreases in photosystem II efficiency. These changes were accompanied by deepoxidation of violaxanthin cycle pigments, suggesting that the absence of trichomes would trigger physiological responses in this species. Our data have revealed different patterns of response of Q. ilex subsp. ballota and Q. coccifera facing the stress conditions prevailing in the Mediterranean area.
Keywords: adaxial epidermis; photoprotection; Quercus; Trichomes

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
Keywords: stomata; taxonomy; Trichomes; waxes

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: stomata; taxonomy; Trichomes; waxes